Shared leadership: A state-of-the-art review and future research agenda - Zhu, Jinlong; Liao, Zhenyu; Yam, Kai Chi; Johnson, Russell E. (Journal of organizational behavior, 2018)
The traditional “great man” approaches to leadership emphasize qualities of individual leaders for leadership success. In contrast, a rapidly growing body of research has started to examine shared leadership, which is broadly defined as an emergent team phenomenon whereby leadership roles and influence are distributed among team members. Despite the progress, however, the extant literature on shared leadership has been fragmented with a variety of conceptualizations and operationalizations. This has resulted in little consensus regarding a suitable overarching theoretical framework and has undermined developing knowledge in this research domain. To redress these problems, we provide a comprehensive review of the growing literature of shared leadership by (a) clarifying the definition of shared leadership; (b) conceptually disentangling shared leadership from other theoretically overlapping constructs; (c) addressing measurement issues; and (d) developing an integrative framework of the antecedents, proximal and distal consequences, and boundary conditions of shared leadership. We end our review by highlighting several new avenues for future research.